Chemometrics-assisted simple UV-spectroscopic determination of carbamazepine in human serum and comparison with reference methods - Cámara, María Silvia (2005)
In the present report, CBZ is determined on real patients samples by using a procedure completely assisted by chemometric tools. Firstly, a response surface methodology based on a mixture design was applied in order to select the best conditions in the extraction step. Finally, multivariate calibration PLS-1 was applied to second derivative UV spectra eliminating a shift baseline effect originated in the extraction procedure. The performance assessment included: a) a three level precision study, b) a recovery study analysing spiked samples, and c) method comparison with HPLC and FPIA methods applied on real patient samples. The results obtained show the potentiality of the presently studied methodology for the following of patients treated with this anticonvulsivant.